(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides information on creative thinking. Creative thinking is the thinking of modern managers, managers, creative thinking is required in business development from the lowest to the highest levels, and it is an instrument of development, growth, development, expansion and moderation, its conscious tool to participate in business development